1993
DOI: 10.1093/geront/33.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Adopting a Disability Approach to Home Care Services for Older Adults

Abstract: The disability and aging communities differ significantly in their perceptions, definitions, and values about the independence and autonomy of disabled individuals. These viewpoints are reflected in the different services and goals of personal assistance provided to older and younger disabled persons. We explore the applicability of the disability approach to personal assistance for older persons and offer ethical, practice-oriented, and political arguments for the aging community to adopt this approach. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Others have argued that one socially determined barrier to the dissemination of consumer-directed models to elders is the lower expectations of professionals, family members, and elderly people themselves about the capacity of older persons to actively manage their own services and to benefit from these (Simon-Rusinowitz & Hofland, 1993). As suggested earlier, to the extent that this is accurate, it suggests another perspective on the findings from this study: Older recipients may not feel more empowered because they may expect relatively little from a more active role in the service relationship; older recipients may have fewer unmet needs because they feel they should be content with less and not complain; and older recipients may not experience service-related changes in their lives because, as they age, they may not expect to experience many benefits even from a helping relationship they have shaped.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Others have argued that one socially determined barrier to the dissemination of consumer-directed models to elders is the lower expectations of professionals, family members, and elderly people themselves about the capacity of older persons to actively manage their own services and to benefit from these (Simon-Rusinowitz & Hofland, 1993). As suggested earlier, to the extent that this is accurate, it suggests another perspective on the findings from this study: Older recipients may not feel more empowered because they may expect relatively little from a more active role in the service relationship; older recipients may have fewer unmet needs because they feel they should be content with less and not complain; and older recipients may not experience service-related changes in their lives because, as they age, they may not expect to experience many benefits even from a helping relationship they have shaped.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research on the experiences of elderly people raises important issues about variations by age in preferences for and experience with self-direction (Doty et al, 1996;Eustis & Fischer, 1992;Hofland, 1988;Kane & Degenholtz, 1997;Simon-Rusinowitz & Hofland, 1993;Simon-Rusinowitz et al, 1997). Scholars have long been interested in autonomy and old age.…”
mentioning
confidence: 99%
“…The same study reported that providers also hold views of clients' interests that reflect age-related stereotypes. Divergent views of aging and disability are also evident in basic clinical practice methods, such as client assessments, where non-elderly individuals with disabilities are assessed on their ability to accomplish tasks with assistance, but assessments for older adults utilize a deficit model that measures their ability to perform tasks unassisted (Simon-Rusinowitz & Hofland, 1993).…”
Section: Lack Of Advocacy For CD By Older Adultsmentioning
confidence: 99%
“…For example, some states have moved to cashing out the benefits for home and community care (Batavia, DeJong, & McKnew, 1991;Cameron & Firman, 1995;Simon-Rusinowitz & Hofland, 1993). The implications of the deep discount applied to this cashing out raise interesting questions about the value consumers place on the service itself.…”
Section: Defining Effectivenessmentioning
confidence: 99%